Evaluation of the Relationship Between the Air-Bone Gap and Prolonged ABR Latencies in Mixed-Type Hearing Loss - Birkent, Omer Faruk; Karlidag, Turgut; Basar, Figen; Yalcin, Sinasi; Kaygusuz, Irfan; Keles, Erol; Akyigit, Abdulvahap (Aves, 2017)
OBJECTIVE: The aim of this study was to determine the air-bone gaps in adults with mixed-type hearing loss using air-conduction auditory brainstem response (ABR) latencies. MATERIALS and METHODS: Thirty adults with mixed-type hearing loss (study group) and 30 adults with normal hearing (control group) were included in this study. Before performing ABR measurements, ear, nose, and throat examinations, pure tone audiometry, speech audiometry, acoustic immittance audiometry, and transient evoked autoacoustic emission testing were performed for all participants. Absolute latencies of I, III, and V waves and interpeak latencies (IPL) at 90 decibel hearing level dB nHL were evaluated and compared with air-bone gap results. RESULTS: ABR latencies using click and tone-burst stimulation were obtained and found to be longer in the mixed-type hearing loss group than in the normal hearing group (p< 0.05). A moderate positive relationship was detected between the air-bone gap and wave III/V latencies at 0.5/1 kHz, I-V/I-III/III-V IPL at 1 kHz. Only one strong relationship was found between 1 kHz air-bone gap and I-V IPL. CONCLUSION: In this study, the magnitude of the air-bone gap could not determined using prolonged ABR latencies. Delays in ABR latencies were observed, but prolonged ABR latencies was not helpful for calculating the air-bone gap on mixed-type hearing loss.
Keywords: Auditory brainstem response; mixed-type hearing loss; air-bone gap